Non-communicable disease policy implementation in Libya: A mixed methods assessment. - Luke N Allen; Cervantée E K Wild; Giulia Loffreda; Mohini Kak; Mohamed Aghilla; Taher Emahbes; Atousa Bonyani; Arian Hatefi; Christopher Herbst; Haider M El Saeh (PLOS Global Public Health)
The Libyan Ministry of Health is keen to understand how it can introduce policies to protect its population from non-communicable diseases (NCDs). We aimed to perform an implementation research assessment of the current situation, including challenges and opportunities. We used an explanatory sequential mixed methods design. We started with a quantitative assessment of NCD policy performance based on review of the WHO NCD Progress Monitor Reports. Once we had identified Libya's NCD policy gaps we performed a systematic review to identify international lessons around barriers and successful strategies for the policies Libya has not yet implemented. Finally, we performed a series of key stakeholder interviews with senior policymakers to explore their perspectives around promising policy actions. We used a realist paradigm, methods triangulation, and a joint display to synthesise the interpretation of our findings and develop recommendations. Libya has not fully implemented any of the recommended policies for diet, physical activity, primary care guidelines & therapeutics, or data collection, targets & surveillance. It does not have robust tobacco policies in place. Evidence from the international literature and policymaker interviews emphasised the centrality of according strong political leadership, governance structures, multisectoral engagement, and adequate financing to policy development activities. Libya's complex political and security situation are major barriers for policy implementation. Whilst some policies will be very challenging to develop and deploy, there are a number of simple policy actions that could be implemented with minimum effort; from inviting WHO to conduct a second STEPS survey, to signing the international code on breast-milk substitutes. Like many other fragile and conflict-affected states, Libya has not accorded NCDs the policy attention they demand. Whilst strong high-level leadership is the ultimate key to providing adequate protections, there are a range of simple measures that can be implemented with relative ease.